A review of the hardware implementation of CRYSTALS-Kyber post-quantum cryptography algorithm - Ardhi Wijayanto; Nabihah Ahmad; Salman Ahmed (Bulletin of Electrical Engineering and Informatics, 2026)
The development of quantum computing is escalating the vulnerability of conventional cryptography algorithms. To answer this challenge, researchers develop the post-quantum cryptography (PQC) algorithms. The PQC algorithms are immune from attacks deployed by quantum computers. CRYSTALS-Kyber (abbreviated as Kyber) is a PQC algorithm, originally constructed as public key encryption (PKE), then extended as the key encapsulation mechanism (KEM) algorithm to securely transfer a shared key to other parties over unsecured communication channels. The implementation of Kyber algorithm in hardware ensures a better security standard for securing systems that prioritize performance. This study provides a literature review of the Kyber hardware implementations. The review is delivered by a systematic literature review method to discuss resource and performance optimization, key design constraints, performance trade-offs, and future research directions in hardware implementation of Kyber based on existing studies. Area utilization and energy efficiency are achieved through the optimization of memory and architecture. The trade-off between performance, flexibility, and utilization remains relevant in the deployment context. Future work should accommodate holistic solutions, security, and performance enhancements as well as fabrication for real-world solutions.